Small and medium-sized enterprise financing in the manufacturing industry: Demand-side determinants of bank credit access in Mozambique - Murambire Júnior, B. J.; Falcão, P. F.; Esperança, J. P. (International Journal of Entrepreneurship and Small Business, 2025)
This paper examines the demand-side factors that influence small and medium-sized enterprises' (SMEs) access to bank financing in the manufacturing industry in Mozambique. A mixed-methods sequential explanatory design was applied, starting with quantitative research on a sample of 347 SMEs followed by qualitative research on 30 SMEs. Managers' experience, firm size, gross profit, and equity were found to be the only statistically significant determinants of SMEs' access to bank credit. The most important themes identified by the qualitative research were risk tolerance, financial literacy, financial management skills, loan terms offered, service quality, lessons learned, cultural aspects, managers' beliefs, and internal aspects. This study fills a research gap by examining the demand-side factors that influence SMEs' access to bank financing in the manufacturing industry in developing economies. The results provide a deeper understanding of which determinants are crucial in order to ensure effective strategies and tools in developing countries. An important implication is that policymakers need to implement holistic approaches that prioritise demand-side factors.